Existence of Solutions for a p-Kirchhoff-Type Problem with Critical Exponent. (9th March 2022) - Benchira, Hayat; El Mokhtar, M. El Mokhtar Ould; Matallah, Atika
Abstract : In this study, we prove the existence of a positive solution for a p -Kirchhoff-type problem with Sobolev exponent.